Reflections on contemporary problems of rehabilitation – theoretical and practical approach - MYDŁOWSKA, Beata (Acta et Commentationes, Sciences of Education, 2026)
Contemporary rehabilitation is evolving dynamically in response to changing social and penitentiary realities. It has shifted from a punitive, isolation-based model toward a supportive approach focused on reintegration, personal development, and strengthening social competences. Modern practices emphasize educational, psychological, and vocational interventions, addressing not only long-term inmates but also those in temporary detention. Despite progress in the Polish system, challenges such as social exclusion and limited post-release support remain. The article highlights the role of rehabilitation—especially work—in preventing recidivism and outlines recommendations to improve its effectiveness in current social conditions.